2018
DOI: 10.1039/c8en00456k
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and transcriptional responses associated with multi-generation exposure of Folsomia candida to engineered nanomaterials

Abstract: This article shows the phenotypic and transcriptional effects of multi-generation nanomaterial exposure to the springtail Folsomia candida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As the field case always involves “multi-generational” exposure, some potential sub-lethal effects of an environmental factor may cumulate over time and become apparent only in a living organism after exposure over multiple generations. Noordhoek et al (2018) found a metal-based nanomaterial tungsten carbide-cobalt affected the reproduction and survival of F. candida from the third generation. By using multi-generational laboratory risk assessments, Bakonyi et al (2011) and Szabó, Seres & Bakonyi (2017) found that F. candida that were fed Cry1Ab expressing maize leaves had some alterations in life-history traits and reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the field case always involves “multi-generational” exposure, some potential sub-lethal effects of an environmental factor may cumulate over time and become apparent only in a living organism after exposure over multiple generations. Noordhoek et al (2018) found a metal-based nanomaterial tungsten carbide-cobalt affected the reproduction and survival of F. candida from the third generation. By using multi-generational laboratory risk assessments, Bakonyi et al (2011) and Szabó, Seres & Bakonyi (2017) found that F. candida that were fed Cry1Ab expressing maize leaves had some alterations in life-history traits and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on RNA-Seq data, Zhang et al (2017b) annotated 32,268 unigenes of the Chinese green mussel ( Perna viridis ) and identified 9,048 differentially expressed genes (DEGs) between exposed and non-exposed groups to cadmium, suggesting a sensitive response of the mussel transcriptome to cadmium. Noordhoek et al (2018) studied phenotypic effects and transcriptional responses in F. candida exposed to nanomaterials and detected physiological alterations cumulating from one generation to the next based on gene expression assays but without visible phenotypic variables.…”
Section: Introductionmentioning
confidence: 99%
“…As the field case always involves "multi-generational" exposure, some potential sub-lethal effects of an environmental factor may cumulate over time and become apparent only in a living organism after exposure over multiple generations. Noordhoek et al (2018) found a metal-based nanomaterial tungsten carbide-cobalt affected the reproduction and survival of F. candida from the third generation. The current one-generation laboratory risk assessment cannot comprehensively evaluate the potential nonlethal chronic effects of Bt toxins on NTOs.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning terrestrial organisms, metal NPs, such as copper oxide and silver, showed mechanisms of toxicity in longer-term exposures that were not predictable based on short-term studies [ 28 , 29 ]. Some longer-term studies assessing the toxicity of different NPs to soil organisms are available (e.g., E. crypticus [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] ( Table 1 ) and Folsomia candida [ 38 ]).…”
Section: Introductionmentioning
confidence: 99%